Relationship between age, BMI, head posture and superficial neck muscle stiffness and elasticity in adult women - Kocur, Piotr (Sci Rep, 2019)
This study determined relationships between age, BMI and cranio-vertebral angle (CVA) (independent variables) and stiffness and elasticity of sternocleidomasteoid [SCM] and upper trapezius [UT] (dependent variables) muscles in sitting posture in 95 women across adult life. Moreover, a stepwise regression was performed to determine to what extent the dependent variables are explained by age, BMI and CVA. Age was moderately correlated with BMI (r = 0.41), and both age and BMI were moderately negatively correlated with CVA (r = −0.54 and −0.55, respectively). High (r = 0.73) and moderate (r = 0.53) linear relationships were present between age and logarithmic decrement (inversely related to elasticity) and stiffness of SCM muscle, respectively. Low (r = 0.36) and moderate (r = 0.47) relationships were present between age and logarithmic decrement and stiffness of UT muscle, respectively. Age accounted for 53% variance in elasticity and 28.5% variance in stiffness of SCM, and for 13% variance in elasticity and 22% variance in stiffness of UT muscle. Introduction of BMI but not CVA to the model explained the variance of these parameters by additional 0–8%. Among the studied factors age is the major correlate of stiffness and elasticity of neck muscles across the adult life.